RANCANG BANGUN SISTEM PENGHITUNG PENGGUNAAN AIR PRABAYAR MENGGUNAKAN MIKROKONTROLER PIC16F877A - Faisal Rahman; Kusworo Adi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
The water recording that still uses manual system has many shortcomings, including error recording by officer, inaccurate of water meter reading, so that many customers feel disadvantaged. The purpose of the research is to make water usage system that can minimalize Mistakes done by the Officers by making prepaid payment system. The water flowed ON flowmeter will rotate the rotor so that it can result clock that becomes input for PIC16F877A to be displayed ON LCD. The number of clock will be characterized with the amount of water that was released so it obtains equation. The equation is put on Program so LCD Output is the amount of water flowed ON flowmeter. The result from Flowmeter characterization is 0.999. The flowmeter test is done by comparing it with standard tools, it obtains correlation coefficient 0,996 with 1,3 % error and test cost is 0.05 %.